Determining the Information Requirements of Electronic Prescribing and Medication Administration System for Cardiovascular Patients - Reza Safdari; Farnoosh Larti; Kamyar Fathi Salari; Saman Mohammadpour (Tehran University of Medical Sciences, 2020)
Background and Aim: Cardiovascular diseases and medication errors are among the leading causes of morbidity and mortality around the world. Electronic prescribing and Medication Administration(ePMA) systems can prevent medication errors to some extent. This study aimed to determine the information requirements of ePMA systems. Materials and Methods: This descriptive study was conducted in Imam Khomeini Hospital of Tehran and School of Allied Medical Sciences affiliated to Tehran University of Medical Sciences (TUMS) in the summer of 2019 in two phases: literature review and survey-based questionnaire. Information items obtained from reviewing the texts of 100 articles were organized in three questionnaires. In the survey phase, questionnaires were distributed among physicians, nurses, and the experts of health information management(HIM) and medical informatics, using census sampling method. The reliability of the questionnaires was measured using Cronbachchr('39')s coefficient alpha. Statistical analysis was done using SPSS. Results: The findings showed that based on specialists' point of view, patientschr('39') demographic information items and unique identifiers gained the highest average, above 4.7. Physicians agreed most with clinical information, including medication history and generic names. From the nurses' point of view, the information items of the patients' problems and the procedures performed and the types of drug doses obtained a complete average of 5. Conclusion: The need for information items varies among different users of ePMA systems, but there may be items that are common for them. Future studies should further investigate financial and pharmaceutical information requirements based on the perspectives of other hospital pharmacy and accounting staff.